Molecular detection of fluoroquinolone-resistant Neisseria meningitidis by using mismatched PCR-restriction fragment length polymorphism technique - Ota, Yusuke; Okada, Reina; Takahashi, Hideyuki; Saito, Ryoichi (Frontiers in Cellular and Infection Microbiology, 2022)
Ciprofloxacin (CIP) is a commonly used antibiotic for meningococcal chemoprophylaxis, and the mutations in the quinolone resistance-determining region of gyrA are associated with CIP-resistant Neisseria meningitidis. Here, we established a mismatched PCR-restriction fragment length polymorphism (RFLP) assay to detect a mutation at codon 91 of gyrA, followed by high-level CIP-resistant meningococci. We designed PCR-RFLP primers to detect the T91I mutation in gyrA by introducing an artificial AciI cleavage site. This assay was performed using 26 N. meningitidis strains whose gyrA sequences have been characterized. The amplified 160 bp PCR product from gyrA was digested into three fragments (80, 66, and 14 bp) when there was no mutation, or two fragments (146 and 14 bp) when there was a mutation at codon 91. A correlation was observed between the mismatched PCR-RFLP assay and gyrA sequencing. This rapid, simple, and accurate assay has the potential to detect CIP-resistant N. meningitidis in clinical microbiology laboratories, contributing to the appropriate antibiotic selection for meningococcal chemoprophylaxis, will help maintain an effective treatment for close contacts of IMD patients, and prevent the spread of CIP-resistant N. meningitidis.